Etiology matters - Genomic DNA Methylation Patterns in Three Rat Models of Acquired Epilepsy - Debski, Konrad J.; Pitkanen, Asla; Puhakka, Noora; Bot, Anna M.; Khurana, Ishant; Harikrishnan, K. N.; Ziemann, Mark; Kaspi, Antony; El-Osta, Assam; Lukasiuk, Katarzyna; Kobow, Katja (Scientific Reports, 2016)
This study tested the hypothesis that acquired epileptogenesis is accompanied by DNA methylation changes independent of etiology. We investigated DNA methylation and gene expression in the hippocampal CA3/dentate gyrus fields at 3 months following epileptogenic injury in three experimental models of epilepsy: focal amygdala stimulation, systemic pilocarpine injection, or lateral fluid-percussion induced traumatic brain injury (TBI) in rats. In the models studies, DNA methylation and gene expression profiles distinguished controls from injured animals. We observed consistent increased methylation in gene bodies and hypomethylation at non-genic regions. We did not find a common methylation signature in all three different models and few regions common to any two models. Our data provide evidence that genome-wide alteration of DNA methylation signatures is a general pathomechanism associated with epileptogenesis and epilepsy in experimental animal models, but the broad pathophysiological differences between models (i.e. pilocarpine, amygdala stimulation, and post-TBI) are reflected in distinct etiology-dependent DNA methylation patterns.
EVALuna2:7321